Air carbon arc gouging and submerged-arc welding: Insights into sensitization and mechanical behavior of AISI 2205 duplex stainless steel - Arthur de Bribean Guerra; Tales Ferreira; Claudemiro Bolfarini; Guilherme Yuuki Koga (Journal of Materials Research and Technology)
Repairing discontinuities and defective welds in AISI 2205 duplex stainless steel (DSS) is a critical procedure of significant technological and scientific interest given the complex metallurgical transformations involved. Air carbon arc gouging (ACAG) is a versatile and cost-effective technique for defect removal across various metals and geometries. However, its application in DSS has been limited due to concerns over sensitization and chloride-induced corrosion risks. This study investigates the effects of ACAG and submerged-arc welding (SAW) on the microstructure, sensitization behavior, and mechanical properties of 2205 DSS. Various gouging parameters and mechanical surface cleaning treatments—as-gouged, brushed, and rectified conditions—were assessed. Microstructural characterization and sensitization assessment were performed using double-loop electrochemical potentiokinetic reactivation (DL-EPR). Additionally, the influence of two weld joint geometries (“X” and “V”) on microstructure, sensitization, and mechanical performance was analyzed. Results indicate that as-gouged surfaces exhibit elevated sensitization risks, while welded joints remain resistant. Mechanical testing demonstrated tensile strengths exceeding 750 MPa in both gouged and welded joints. This study provides new insights into optimizing ACAG and SAW repair strategies for 2205 DSS, particularly for applications in the petrochemical and offshore industries.